Kinetic and mechanical analysis of live tube morphogenesis. - Cheshire, A.M.; Kerman, B.E.; Zipfel, W.R.; Spector, A.A.; Andrew, D.J. (Developmental Dynamics, 2008)
Ribbon is a nuclear Broad Tramtrack Bric-a-brac (BTB) -domain protein required for morphogenesis of the salivary gland and trachea. We recently showed that ribbon mutants exhibit decreased Crumbs and Rab11-coincident apical vesicles and increased apical Moesin activity and microvillar structure during tube elongation. To learn how these molecular and morphological changes affect the dynamics of tubulogenesis, we optimized an advanced two-photon microscope to enable high-resolution live imaging of the salivary gland and trachea. Live imaging revealed that ribbon mutant tissues exhibit slowed and incomplete lumenal morphogenesis, consistent with previously described apical defects. Because Moesin activity correlates with cortical stiffness, we hypothesize that ribbon mutants suffer from increased apical stiffness during morphogenesis. We develop this hypothesis through mechanical analysis, using the advantages of live imaging to construct computational elastic and analytical viscoelastic models of tube elongation, which suggest that ribbon mutant tubes exhibit three- to fivefold increased apical stiffness and twofold increased effective apical viscosity.